PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS 2 SD PADA PELAJARAN MATEMATIKA MATERI PENGUKURAN - Nisa Saumarwah; Arie Rakhmat Riyadi; Haviz Kurniawan (CV. Adiba Aisha Amira, 2025)
This research aims to improve students’ mathematics learning outcomes through the application of demonstration learning methods. The method used was Classroom Action Research (PTK) which was carried out in two cycles. The research subjects were 2nd grade students at SDN 053 Cisitu, totaling 30 students, consisting of 15 women and 15 men, while the research object was the student’ mathematics learning outcomes. Data was collected through tests which were analyzed to measure students’ understanding with success indicators reaching 80%. The research results showed a significant increase in students’ understanding, with an average understanding in the first cycle of 74,16% and increasing to 74,16% in the second cycle. Thus, there was an increase in students’ understanding by 14,2%. the implication of this research is that the application of the demonstration learning method is effective in improving students’ mathematics learning outcomes, especially at the elementary school level.